PENGARUH HARGA, PROMOSI, DAN KUALITAS PRODUK TERHADAP KEPUTUSAN PEMBELIAN KONSUMEN INDOMIE PADA PT. ALAMJAYA WIRASENTOSA KABANJAHE - Fenny Krisna Marpaung; Markus Willy Arnold Simarmata; Asyifa Sofira; Silvia Aloyna (JURNAL MANAJEMEN, 2021)
This study aims to determine the effect of price, promotion and product quality on purchasing decisions. In this study, primary data was obtained by giving a questionnaire by asking a number of questions to the respondent. The number of respondents in this study were 115 people. The data analysis technique used multiple linear analysis. The value of Adjusted R Square was 56.7%. This means independent variables; price (X1), promotion (X2) and product quality (X3) can explain 56.7% on the purchasing decisions variable (Y). Meanwhile, the remaining 43.3% is explained by other factors not included in this study. Based on the results of the statistical analysis, partially shows that price, promotion and product quality have a positive and significant influence on purchasing decisions. Based on the F test it can be seen that Fhitung (50.667) > Ftabel (2.69) and the significance level is 0.000 <α (0.05). This means, simultaneously showing that there is a significant influence between price, promotion and product quality on purchasing decisions.